Social Media Marketing dan Online Customer Review Terhadap Brand Attitude dan Dampaknya pada Purchase Intention pada Product Smartphone - Farizil Qudsi, Maulana; Mardhiyah, Dien (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine and analyze the influence of social media marketing and online customer reviews on brand attitude, and their impact on purchase intention for the OPPO Find N5 Fold product. This research employs a quantitative approach with exogenous variables including Social Media Marketing (X1) and Online Customer Review (X2), and endogenous variables comprising Brand Attitude (Z) and Purchase Intention (Y). Primary data were collected using a five-point Likert scale questionnaire, distributed to respondents residing in Surabaya who do not yet own an OPPO Find N5 Fold, are active on social media, and have seen advertisements or reviews of the product. A purposive sampling technique was applied, with a total of 130 respondents. Data were analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS) via SmartPLS 4.0.9. The findings reveal that both social media marketing and online customer reviews have a positive and significant effect on brand attitude, which in turn positively influences purchase intention toward the OPPO Find N5 Fold. Therefore, companies are encouraged to develop creative communication strategies on social media and manage customer reviews strategically to strengthen brand perception and drive purchase intention.